2019
DOI: 10.1002/gcc.22825
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characteristics of terminal deoxynucleotidyl transferase negative precursor B‐cell phenotype Burkitt leukemia with IGH‐MYC rearrangement

Abstract: Precursor B cell phenotype Burkitt lymphoma/leukemia with IGH-MYC is a rare subtype of Burkitt lymphoma (BL). BL and B lymphoblastic leukemia/lymphoma (B-ALL/ LBL) differ as regards treatment and the distinction between these two entities is crucial. Patients demonstrating a terminal deoxynucleotidyl transferase (TdT)-positive precursor B cell phenotype with IGH-MYC rearrangement have been reported to be molecularly distinct from BL and closer to B-ALL/LBL. We investigated the molecular characteristics of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Taken together with the IGHJ3 breakpoint on the IGH side, t(8;14)(q24;q32)/MYC-IGH in this case likely occurred at an early B-cell stage in the BM, in contrast to t(8;14)(q24;q32)/MYC-IGH in the majority of cases of sporadic BL that occurred in GC. Nevertheless, as reported MYC breakpoints were distributed over a large region encompassing the MYC coding exons (Table 1), 2,4 further studies are required to confirm the validity of the CpG breakage model in precursor B-cell BL.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Taken together with the IGHJ3 breakpoint on the IGH side, t(8;14)(q24;q32)/MYC-IGH in this case likely occurred at an early B-cell stage in the BM, in contrast to t(8;14)(q24;q32)/MYC-IGH in the majority of cases of sporadic BL that occurred in GC. Nevertheless, as reported MYC breakpoints were distributed over a large region encompassing the MYC coding exons (Table 1), 2,4 further studies are required to confirm the validity of the CpG breakage model in precursor B-cell BL.…”
Section: Discussionmentioning
confidence: 97%
“…Although precursor B-cell BL has been described primarily in the pediatric literature, 6,7 this report confirmed that this rare type of BL can occur in the adult population (Supplementary Table S1). [1][2][3][4][5]8,9 As t(8;14)(q24;q32)/MYC-IGH breakpoints in sporadic cases of BL occur nearby or within MYC exon 1, which is a target of somatic hypermutation (SHM), 20 and within the switch regions of IGH, the translocation has been considered to be mediated by the SHM/class switch recombination (CSR) mechanism in the GC. 1,2 However, as BL cells of this case exhibited a precursor B-cell immunophenotype and carried unmutated IGH V-D-J sequences, it is unlikely that the SHM/CSR machinery was active.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations